Menumbuhkan Akar Iman: Pendekatan Kreatif Membawa Kitab Suci ke Hati Anak-Anak - Herelius Nius; Gregorius Daru Wijoyoko; Istoto Raharjo (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Faith is an essential foundation in the spiritual life of Christians, and nurturing faith in children is a collective responsibility among the family, the church, and society. This article will discuss creative approaches that can be used to bring the Scriptures to the hearts of children. A literature review approach is used in writing the article in order to develop a deep understanding to increase their understanding of the teachings of the faith, also to foster a deep love and appreciation for the Scriptures as the Word of God. The article concludes that through the use of stories, games, art, music, and technology, we can create a fun and inspiring environment for children to encounter the Scriptures and develop their faith.